2018
DOI: 10.1021/acs.jctc.8b00292
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic-Energy Density-Functional Theory on a Lattice

Abstract: We present a kinetic-energy density-functional theory and the corresponding kinetic-energy Kohn–Sham (keKS) scheme on a lattice and show that, by including more observables explicitly in a density-functional approach, already simple approximation strategies lead to very accurate results. Here, we promote the kinetic-energy density to a fundamental variable alongside the density and show for specific cases (analytically and numerically) that there is a one-to-one correspondence between the external pair of on-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 65 publications
(136 reference statements)
1
32
0
Order By: Relevance
“…Surprisingly, we have found that for these systems the global interpolations always outperform their local counterparts, in striking contrast with what had been observed so far for small chemical systems [14,15]. We have also compared two different definitions of the kinetic correlation energy density, which plays a crucial role for strongly correlated systems [28,29], and that can help in understanding how to extend to the continuum a KS theory that recovers the exact kinetic energy density recently proposed for lattice models [54].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Surprisingly, we have found that for these systems the global interpolations always outperform their local counterparts, in striking contrast with what had been observed so far for small chemical systems [14,15]. We have also compared two different definitions of the kinetic correlation energy density, which plays a crucial role for strongly correlated systems [28,29], and that can help in understanding how to extend to the continuum a KS theory that recovers the exact kinetic energy density recently proposed for lattice models [54].…”
Section: Discussionmentioning
confidence: 67%
“…Here we compare the features of these two definitions, as the correlation kinetic energy is important to capture strong correlation. Also, very recently, it has been proposed to use the correlated kinetic energy density as an additional variable in an extended KS DFT theory for lattice hamiltonians [54], and it is thus important to understand which definition is the most suitable to generalize this theory to the continuum.…”
Section: Kinetic Correlation Energy Densitiesmentioning
confidence: 99%
“…The common approach is to approximate the energy expression E[n] − E s [n] and then obtain the corresponding Hxc potential via functional derivative with respect to n(z). However, for the case of certain more complex functional variables like the kinetic-energy density K(z, z ), the usual approach via the energy is no longer viable [32]. In this case the above procedure becomes instrumental to go beyond the few simple approximations known.…”
Section: Using Density-matrix Embedding Theory In Density-functional Theories: a Novel Approximation Schemementioning
confidence: 99%
“…The quantity we look at here specifically is the kinetic-energy density (for a definition of a Hubbard-type of Hamiltonian see Ref. [27] and in a continuum setting Ref. [28] (Chapter 8)).…”
Section: Using Density-functional Mappings In Density-matrix Embeddin...mentioning
confidence: 99%
“…The advantage of the kinetic-energy density with respect to the 1RDM is that it does not suffer from the idempotency issue, i.e. in general a non-interacting system can share the same ground-state kinetic-energy density as an interacting one [27]. However, the second question to make such a procedure well-defined is, whether the mapping between density and kinetic-energy density and local as well as non-local potential is one-to-one, i.e.…”
Section: Using Density-functional Mappings In Density-matrix Embeddin...mentioning
confidence: 99%